The Unbreakable Relations Between Indonesia-Vietnam Post â€œSink the Vesselsâ€ Policy: A Complex Systems Approach - Kantaprawira, Rusadi; Bainus, Arry; Kusumawardhana, Indra (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
The vibrant bilateral relations between Indonesia-Vietnam has been tested by the Sink the Vessels policy, a robust measure executed by Indonesia to tackle rampant illegal fishing that encroach Indonesian waters. The policy has caused in the demolition of, among else, Vietnamese fishing vessels; and has also led to near-clash and incidents at sea. Despite these, both countries bilateral relations were far from hostile condition, and uphold their neighbourly relations to manage the illegal fishing problem. How Could Indonesiaâ€™s foreign policy action did not further exacerbate Indonesia-Vietnam relations post â€œSink the Vesselsâ€ policy? To tackle our question, this article probes to describe the complex systems that interwoven Indonesia and Vietnam during the rising tension. We argue that the complex systems encapsulated Indonesia â€“ Vietnam relations post â€œSink the Vesselsâ€ policy consist of symbol system, interest system, and role system that maintain their friendly bilateral relations, even in the turbulence ocean. This article exposes that Indonesia-Vietnam responds to tackle the problem stems primarily from the linkage between the three systems to escape the security dilemma.